The Israeli Factor in Iran-Azerbaijan Relations (2005-2013) - Armen Israyelyan (Banber Arevelagitut'yan Instituti)
The article deals with Israel’s factor which influences Iran-Azerbaijan relations. The article highlights the following issues when assessing the impact of the Israeli factor on Iran-Azerbaijan relations:  Represent Israel’s foreign policy priorities on Azerbaijan,  Assess the position of the Islamic Republic of Iran on Azerbaijan-Israel cooperation and analyze Iran's policy within this context,  Analyze Azerbaijan's motives for strengthening cooperation with Israel. The nuclear program, Iran's missile systems, the Shia factor, the Iranian-speaking peoples of Azerbaijan (Tats, Talish), the activities of Azerbaijani Shia opposition figures, the 760-kilometer border between Azerbaijan and Iran – these are the main factors underlying Israel's policy towards Azerbaijan. Azerbaijan first of all justified the establishment of relations with Israel with the expectation of receiving military-political assistance from Israel in the settlement of the Nagorno Karabakh conflict.